2017
DOI: 10.1111/jcpe.12720
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast growth, after cleaning of biofilm‐covered titanium discs with air‐polishing and cold plasma

Abstract: An AP treatment has the potential to remove biofilm from rough implant surfaces completely. In contrast to our hypothesis, the combination of plasma and AP treatment did not enhance osteoblast spreading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(69 citation statements)
references
References 44 publications
8
61
0
Order By: Relevance
“…After reading the full‐text articles, 10 articles were excluded: three articles due to using the AA in combination with other decontamination methods, one study was not about titanium surface, two articles did not use AA for decontamination, one study was not in English and not published in a peer‐review journal, one study used the AA powder in an antimicrobial solution but did not use the AA device, one study had an in vivo design with decontamination procedures taking place in the beagle dogs, and the full text for one study was not retrieved . The 48 included articles were ultimately processed for data extraction . The summary of the search strategy is depicted in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After reading the full‐text articles, 10 articles were excluded: three articles due to using the AA in combination with other decontamination methods, one study was not about titanium surface, two articles did not use AA for decontamination, one study was not in English and not published in a peer‐review journal, one study used the AA powder in an antimicrobial solution but did not use the AA device, one study had an in vivo design with decontamination procedures taking place in the beagle dogs, and the full text for one study was not retrieved . The 48 included articles were ultimately processed for data extraction . The summary of the search strategy is depicted in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the 48 selected studies have been reported in chronological order in Table . It is noteworthy to mention that out of 48 included studies, only 11 studies employed devices to standardize the decontamination procedure and avoid the clinician erroneous, and only one study used a phantom head to simulate clinical conditions …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to note that killing the biofilm is not enough for its removal, considering there are other biofilm products that play a role in peri‐implantitis, including cytokines . It was demonstrated that removal of dead microbial residues was equally necessary to promote cell adhesion . The visual analysis of the confocal images of the present study showed fewer microorganisms in plasma‐treated samples than in negative control groups.…”
Section: Discussionmentioning
confidence: 54%
“…Although these findings indicate a possible mechanical removal of dead biofilm, the LTP potential to remove dead bacterium is still controversial. A recent study used 7‐day‐old biofilms to investigate the cleaning efficacy of air polishing with or without additional cold plasma treatment and concluded that concomitant use of air polishing and plasma treatment did not enhance osteoblast spreading …”
Section: Discussionmentioning
confidence: 99%